ZB Bank Digital Channels - Muguse, Tony T. (Midlands State University, 2018)
ZB Bank Digital Channels is a system that uses the internet as the delivery channel to conduct banking activity, for example, transferring funds, paying bills, viewing savings account balances, applying for loans and ordering ATM cards. This system targets the clients and various departments in the bank (Corporate banking, Retail banking, Treasury and Investment banking) and production of reports for all the levels of management. The purpose of this project was to come up with an efficient and effective ZB Bank Digital Channels system to meet clients’ needs. This project was done in five main phases, which include Introduction, Planning, Analysis, Design and Implementation Phases. The introduction phase is an introduction of the research study and a historical background of the organization. The planning phase details the scheduling of the study and a feasibility study which was conducted to evaluate viability of the system. From the feasibility study, the project proved to be feasible. During the analysis phase, the researcher analyzed the weaknesses and strengths of the current or existing system and evaluated whether to develop, improve or outsource the software. User requirements were gathered using questionnaires, interviews and observations. After analysis phase, the design phase followed. A database was designed using MySQL Database management system, input forms, menus and output forms using diagrams to illustrate the major functionalities of the ZB Bank Digital Channels. The last phase was implementation, were the implementation of the proposed system and testing and maintenance were carried out continuously identifying and rectifying any errors. Parallel conversion was recommended when the project was implemented.